2010
DOI: 10.1128/jcm.01694-09
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis Identifies Human Adenovirus Type 55 as a Re-Emergent Acute Respiratory Disease Pathogen

Abstract: Novel human adenoviruses (HAdVs) arise from genome recombination. Analysis of HAdV type 55 from an outbreak in China shows a hexon recombination between HAdV-B11 and HAdV-B14, resulting in a genome that is 97.4% HAdV-B14. Sporadic appearances as a re-emergent pathogen and misidentification as "HAdV-B11a" are due to this partial hexon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
256
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(265 citation statements)
references
References 21 publications
7
256
0
2
Order By: Relevance
“…The cases increased during spring and winter, and seasonal distribution was different depending on the species. The possibility of adenovirus co-infection should be closely monitored in the surveillance because natural recombination could occur between the same species (13,18). These findings provide insights into the epidemiology of HAdV infections in Japan.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cases increased during spring and winter, and seasonal distribution was different depending on the species. The possibility of adenovirus co-infection should be closely monitored in the surveillance because natural recombination could occur between the same species (13,18). These findings provide insights into the epidemiology of HAdV infections in Japan.…”
mentioning
confidence: 99%
“…Epidemic levels of HAdV-B7 have been low in the recent years in Japan, and detection of both HAdV-B14 and -B55 has not been reported thus far (http: www.nih.go.jp niid en iasr-e.html). Acute respiratory diseases are typically caused by HAdV-E4, -B7, -B14, and -B55 (11)(12)(13). HAdV-D has occasionally been reported as a cause of respiratory infections (14), and molecular epidemiological study of HAdVs associated with epidemic keratoconjunctivitis showed circulation of HAdV-D37 and -D53 in Osaka (5).…”
mentioning
confidence: 99%
“…To date, 55 different serotypes have been identified and grouped into seven different species (Human Adenovirus A through Human Adenovirus G) (13,14,30,31). In immunocompetent patients, adenovirus infections lead to benign enteric or respiratory symptoms; and direct diagnosis of local infection by cell culture, indirect immunofluorescence, or immunochromatography is adequate (25).…”
mentioning
confidence: 99%
“…Le séquençage de HAdV-D53 a révélé qu'il proviendrait de recombinaisons génétiques entre les souches HAdV-D22, HAdV-D8 et HAdV-D37 [42]. Ces dernières années, la littérature révèle un grand nombre de réarrangement génomique entre les différents HAdV expliquant en partie la voie évolutive des HAdV [43][44][45][46]. En revanche, ce processus de recombinaison génétique n'est pas restreint aux HAdV.…”
Section: Mécanismes Moléculaires Pour L'émergence De Zoonosesunclassified